Penerapan Sekolah Ramah Anak dalam Pembentukan Karakter Peserta Didik di SMA Negeri - Sermila Sermila; Mustaring Mustaring; Andi Aco Agus (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2026)
This study aims to examine: (1) the implementation of Child-Friendly School content standards in shaping students’ character at SMA Negeri 1 Soppeng; (2) the learning processes that support students’ character development; and (3) the supporting and inhibiting factors in the implementation of Child-Friendly Schools. This research employed a qualitative approach with a descriptive method. The informants consisted of 11 participants. Data were collected through observation, interviews, and documentation. The results show that the implementation of Child-Friendly School content standards has been carried out effectively through positive discipline, an adaptive curriculum, and student involvement in school programs, which contribute to the development of responsibility, discipline, independence, and cooperation. The learning process also supports character building through the integration of character values, the application of Child-Friendly School principles, and the use of appropriate teaching methods. Supporting factors include school commitment, co-curricular and extracurricular activities, school culture, and teachers’ role modeling, while inhibiting factors include diverse student characteristics, generational gaps, and limited parent-school collaboration. The findings imply that consistent implementation of Child-Friendly Schools can strengthen character development at the senior high school level.